Efficiency Analysis of Fur Shellfish Marketing Channels (AnaDara Antiquata) in the City of Tanjung Balai - Kinanti, Mentari; Aslami, Nuri; Marliyah, Marliyah (Journal of Management and Business Innovations, 2023)
This research aims to find out what types of marketing channel patterns have been identified and to find out the level of efficiency of marketing channels that are more efficient in marketing feather shells (anadara antiquata) in Tanjung Balai City. The approach method in this research is a qualitative approach with descriptive research type. The data sources used are primary data obtained by interviews and direct observation and secondary data obtained from related documents. The location of this research was carried out in Tanjung Balai considering the large number of feather clam fishermen. The research results show that marketing channel I is efficient because the percentages are 2.85% and 1.92% and for channel II the percentage is 2.38% and for marketing channel III the percentage is 7.42%. If we look at the three existing marketing channels as a whole, marketing channel II is the most efficient with a percentage of 2.38% but can only be sold. Keywords: Analytics, Efficiency, Marketing Channels.